2017
DOI: 10.1080/2162402x.2017.1338997
|View full text |Cite
|
Sign up to set email alerts
|

Dosing immunotherapy combinations: Analysis of 3,526 patients for toxicity and response patterns

Abstract: Immunotherapy combinations are used to improve outcomes in metastatic cancer, but evidence-based knowledge of appropriate starting doses for novel combinations is lacking. Phase I-III adult combination clinical trials (≥ 1 drug was immunotherapy; anti-PD-1, PD-L1, or CTLA-4) were reviewed (PubMed Jan 1, 2010 to Sep 1, 2016; ASCO 2014-2016, ASH/ESMO 2014-2015 abstracts). The safe dose for each drug used in each combination was divided by the single-agent recommended dose to calculate dose percentage. Additive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…However, recent advances in NGS and molecular profiling have demonstrated that each tumor has a unique molecular profile, which mandates a more personalized approach . Recent studies have explored dosing of novel combinations of targeted agents, cytotoxics and immunotherapies . The FDA recently approved pembrolizumab in a tissue‐agnostic manner for use in all patients with MSI‐H status or mismatch gene alterations, which signifies a major shift in drug approval practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent advances in NGS and molecular profiling have demonstrated that each tumor has a unique molecular profile, which mandates a more personalized approach . Recent studies have explored dosing of novel combinations of targeted agents, cytotoxics and immunotherapies . The FDA recently approved pembrolizumab in a tissue‐agnostic manner for use in all patients with MSI‐H status or mismatch gene alterations, which signifies a major shift in drug approval practice.…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of immunotherapy and cytotoxic chemotherapy are increasingly being used and tested in clinical trials . Chemotherapy has the potential to enhance antitumor immune responses by several mechanisms including activation of immune effectors such as monocytic‐derived dendritic cells and sensitizing tumor cells to lysis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[301][302][303] Thus, current anticancer drugs have been developed in immunodeficient preclinical models and in clinical trials devoid of any form of immunomonitoring, mainly most often aimed at identifying maximum tolerated doses (MTDs). 298,304 Nonetheless, a majority of currently available anticancer agents mediate on-target or off-target immunostimulatory effects, which strongly argues against an irrelevant role for the immune system in the therapeutic effects of these treatments. [305][306][307][308] Moreover, in various cases, chemotherapeutics applied through multiple treatment cycles may negatively affect the immune system, by causing lymphopenia or leucopenia, thereby further compromising antitumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the widespread use of these treatments has been implemented mostly on empirical (rather than immunological) grounds. 200,[296][297][298][299][300] Indeed, the possibility that chemotherapy and other forms of treatment (including radiotherapy and photodynamic therapy) might promote an immunogenic form of cancer cell death has been overlooked for several decades. [301][302][303] Thus, current anticancer drugs have been developed in immunodeficient preclinical models and in clinical trials devoid of any form of immunomonitoring, mainly most often aimed at identifying maximum tolerated doses (MTDs).…”
Section: Discussionmentioning
confidence: 99%